Data Warehouse Modeling Using Online Analytical Processing Approach - Galih Budianto (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2022)
Increasing business needs affect business competition in many companies that utilize information technology. The competition aims to gain advantages that utilize information technology in facilitating business processes. One of the conveniences offered is the use of information technology to support decision making in carrying out existing business processes in middle-to-upper scale companies that have large amounts of data. Online Analysis Processing (OLAP) is an approach method to present answers to the demand for a dimensional analysis process quickly, namely the design of applications and technologies that can collect, store, manipulate multidimensional data for analyst purposes. Information delivery generated from Online Analysis Processing (OLAP) can help executive information systems in generating sales reports because it has a response time of 0.0038769999519 seconds.